SEGMENTAL ANALYSIS OF DIASTOLIC DYSFUNCTION OF THE LEFT VENTRICLE IN MYOCARDIAL POSTINFARCTION FOCAL CHANGES - D. A. Shvets; S. V. Povetkin (Российский кардиологический журнал)
Aim. Comparison of diagnostical abilities of tissue Doppler (TD) and speckle tracking (ST) for assessment of segmental diastolic dysfunction in postinfarction focal changes of myocardium (PIFC) of LV.Material and methods. Totally, 137 CHD patients studied. In analysis of TD and ST we assessed peaks of early and delayed transmitral LV fillings. Assessment of transmitral parameters of diastolic dysfunction was done with common approach.Results. The study showed that in PIFC persons there is no significant differences by most of transmitral flow parameters and TD. Strain rate assessment of myocardial deformation and ST led to conclusion on mostly delayed filling peak decrease, which is one of the signs of segmental diastolic dysfunction of the LV in PIFC.Conclusion. TD and ST make it to reveal covert disorders of diastolic LV relaxation in PIFC patients with absence of diastolic dysfunction criteria by TMBF.